Distinct skeletal muscle molecular responses to pulmonary rehabilitation in chronic obstructive pulmonary disease: a cluster analysis. Issue 2 (18th January 2019) - Kneppers, Anita E.M.; Haast, Roy A.M.; Langen, Ramon C.J.; Verdijk, Lex B.; Leermakers, Pieter A.; Gosker, Harry R.; van Loon, Luc J.C.; Lainscak, Mitja; Schols, Annemie M.W.J.
Abstract: Background: Pulmonary rehabilitation (PR) is a cornerstone in the management of chronic obstructive pulmonary disease (COPD), targeting skeletal muscle to improve functional performance. However, there is substantial inter‐individual variability in the effect of PR on functional performance, which cannot be fully accounted for by generic phenotypic factors. We performed an unbiased integrative analysis of the skeletal muscle molecular responses to PR in COPD patients and comprehensively characterized their baseline pulmonary and physical function, body composition, blood profile, comorbidities, and medication use. Methods: Musculus vastus lateralis biopsies were obtained from 51 COPD patients (age 64 ± 1 years, sex 73% men, FEV1, 34 (26–41) %pred.) before and after 4 weeks high‐intensity supervised in‐patient PR. Muscle molecular markers were grouped by network‐constrained clustering, and their relative changes in expression values—assessed by qPCR and western blot—were reduced to process scores by principal component analysis. Patients were subsequently clustered based on these process scores. Pre‐PR and post‐PR functional performance was assessed by incremental cycle ergometry and 6 min walking test (6MWT). Results: Eight molecular processes were discerned by network‐constrained hierarchical clustering of the skeletal muscle molecular rehabilitation responses. Based on the resulting process scores, four clusters of patients were identified by hierarchical cluster analysis. Two major patient clusters differed in PR‐induced autophagy ( P < 0.001), myogenesis ( P = 0.014), glucocorticoid signalling ( P < 0.001), and oxidative metabolism regulation ( P < 0.001), with Cluster 1 (C1; n = 29) overall displaying a more pronounced change in marker expression than Cluster 2 (C2; n = 16). General baseline characteristics did not differ between clusters. Following PR, both 6 min walking distance (+26.5 ± 8.3 m, P = 0.003) and peak load on the cycle ergometer test (+9.7 ± 1.9 W, P < 0.001) were improved. However, the functional improvement was more pronounced in C1, as a higher percentage of patients exceeded the minimal clinically important difference in peak workload (61 vs. 21%, P = 0.022) and both peak workload and 6 min walking test (52 vs. 8%, P = 0.008) upon PR. Conclusions: We identified patient groups with distinct skeletal muscle molecular responses to rehabilitation, associated with differences in functional improvements upon PR.